Odstępstwa od normy w tłumaczeniach z języka ukraińskiego i rosyjskiego na polski autorstwa młodzieży wielojęzycznej na Ukrainie .......... 239 - Zielińska, Maria (Tożsamość na styku kultur: 4, 2021)
THE DEVIATIONS FROM THE NORM IN TEXTS TRANSLATED FROM UKRAINIAN AND RUSSIAN INTO POLISH BY YOUNG MULTILINGUALS IN UKRAINE The author of the article analyzes selected language and communication peculiarities based on short texts translated from Ukrainian and Russian into Polish by students attending Polish schools in Lviv and Horodok. The influence of East Slavic languages on the Polish language of young people was traced. The most frequent deviations from the Polish grammar and lexical norms caused by interference and, to a lesser extent, imprecision and superficial translation were analyzed.